(untitled) (Al-Academy, 2023)
The research aims to study the effect of adding (Li2O) to an alkaline glaze containing (K2O, Na2O). Although all the alkaline oxides have common properties, each oxide has something that distinguishes it. The molecular weight of (Li2O) is two times less than that of (Na2O) and three times that of (K2O). Therefore, it is added in small proportions. In addition, it is a very strong flux, so it is not used alone, but rather replaces a part of other alkaline oxides. It was added to an alkali glass that matured at a temperature of 980CO in proportions (2.0,1.4,1.2,0.8,0.4%) instead of (Na2O), using lithium carbonate (Li2CO3) as an oxide source. The glazes mixtures were applied to a white pottery body, and the samples were fired and cooled according to programmed timings. After that, the tests and calculations were carried out: virtual and microscopic examinations, density, viscosity, surface tension, thermal expansion, hardness and scratch resistance. After analyzing and discussing the results, it was found that (Li2O) has varying effects on the properties of glazes, some of which are effective and others are less effective